Sharia equity funds performance throughout bullish and bearish market in Indonesia stock exchange - Marsono, A. Dewantoro (Islamic Business School, 2017)
The purpose of this study is to examine the performance of sharia equity funds in bullish and bearish market conditions.The sample consists of eight sharia equity funds already existed in the market for more than five years. Data was taken from the period 2012-2016.Market condition was evaluated by a moving average model, and the sharia equity funds performance in each market condition was evaluated by the Treynor index model.The result shows that the sharia equity funds performance can beat the market in bearish market condition, but not in bullish and combined market conditions.However, each sharia equity fund exhibits different performance. Knowing the performance of sharia equity funds in various market conditions will benefit the investors, as they can set up new strategies in managing their portfolio to generate more profits in the future.